Protocol of the Fit-For-Fertility study: a multicentre randomised controlled trial assessing a lifestyle programme targeting women with obesity and infertility. Issue 4 (19th April 2022) - Belan, Matea; Gélinas, Myriam; Carranza-Mamane, Belina; Langlois, Marie-France; Morisset, Anne-Sophie; Ruchat, Stephanie-May; Lavoie, Kim; Adamo, Kristi; Poder, Thomas; Gallagher, Frances; Pesant, Marie-Hélène; Jean-Denis, Farrah; et al.
Abstract : Introduction: Women with obesity are at a higher risk of infertility as well as gestational and neonatal complications. Lifestyle changes are universally recommended for women with obesity seeking fertility treatments, but such intervention has only been assessed in very few robust studies. This study's objectives are therefore to assess the clinical outcomes and cost-effectiveness of an interdisciplinary lifestyle intervention (the Fit-For-Fertility Programme; FFFP) targeting women with obesity and subfertility in a diverse population. Methods and analysis: This pragmatic multicentre randomised controlled trial (RCT) will include 616 women with obesity (body mass index ≥30 kg/m 2 or ≥27 kg/m 2 with polycystic ovary syndrome or at-risk ethnicities) who are evaluated at a Canadian fertility clinic for subfertility. Women will be randomised either to (1) the FFFP (experimental arm) alone for 6 months, and then in combination with usual care for infertility if not pregnant; or (2) directly to usual fertility care (control arm). Women in the intervention group benefit from the programme up to 18 months or, if pregnant, up to 24 months or the end of the pregnancy (whichever comes first). Women from both groups are evaluated every 6 months for a maximum of 18 months. The primary outcome is live birth rate at 24 months. Secondary outcomes include fertility, pregnancy and neonatal outcomes; lifestyle and anthropometric measures; and cost-effectiveness. Qualitative data collected from focus groups of participants and professionals will also be analysed. Ethics and dissemination: This research study has been approved by the Research Ethics Board (REB) of Centre intégré universtaire de santé et des services sociaux de l'Estrie—CHUS (research coordinating centre) on 10 December 2018 and has been or will be approved successively by each participating centres' REB. This pragmatic RCT will inform decision-makers on improving care trajectories and policies regarding fertility treatments for women with obesity and subfertility. Trial registration number: NCT03908099 . Protocol version: 1.1, 13 April 2019